Religious Beliefs, Religious Contexts, and Perceived Interactions with Ex-Offenders - Yelderman, Logan A. (Review of religious research, 2018)
Religious institutions can provide a means of support and resources for many people, particularly, individuals who have criminal histories, specifically parolees, sex offenders, and insanity acquittees. When these individuals are released into the community, they often face difficulties in acquiring shelter, work, and social support. Out of their own volition or as a result of faith-based prison programs, they might turn to religious institutions for help reintegrating into the community. However, whether congregation members are more or less accepting of these individuals is unaddressed in the current literature. Two studies assess the relationship between religious beliefs, religious contexts, legal attitudes, and perceived social interactions with parolees, sex offenders, and insanity acquittees. Results suggest that religious beliefs, legal attitudes, and religious contexts play an important role in individuals' perceived interactions with these individuals. Religious contexts, specifically, might facilitate more positive social interactions with parolees. Implications are discussed.